Organizational Citizenship Behavior Among Employees in Indonesian and Malaysian Higher Education Institutions - Retno Dwiyanti; Pambudi Rahardjo; Imam Faisal Hamzah; Junaidah Yusof (Journal of Innovation in Educational and Cultural Research, 2024)
Organizational citizenship behavior is one of the positive behaviors that employees in higher education need to have because it can have a positive impact on employees and educational institutions beyond what is expected. This research aims to determine the contribution of the organizational citizenship behavior aspect in reflecting/measuring the most dominant organizational citizenship behavior in employees at Indonesian universities and employees at Malaysian universities. The research subjects were lecturers and employees of Universitas Muhammadiyah Purwokerto and Universiti Teknologi Malaysia. The research results show that the Indonesian and Malaysian versions of the organizational citizenship behavior scale are valid and reliable. The scale can be utilized optimally as a tool for measuring organizational citizenship behavior in university employees in Indonesia and Malaysia. Further results show that organizational citizenship behavior can be reflected in four aspects, namely altruism, sportsmanship, organizational compliance, and loyalty. Organizational citizenship behavior among employees in Indonesian universities shows the most dominant dimensions of altruism and sportsmanship reflecting organizational citizenship behavior, while organizational citizenship behavior among employees in Malaysian universities shows all the dominant dimensions in reflecting organizational citizenship behavior, namely altruism, sportsmanship, organizational compliance, and loyalty. The findings of this research can contribute to higher education organizations to develop citizenship behavior both individually and in organizations that can encourage the performance of higher education employees in Indonesia and Malaysia.